FLIPing failure into resilience - McVanel, Sarah (Operating Room Nurses Association of Canada Journal, 2021)
Has there ever been a time when, collectively, we have been called to level up our lives, push past our knowledge threshold, and face hard truths? And hasn’t this triggered the buried memories of other challenging experiences – that former bully boss, that near miss with a patient, a stormy time with our teen – and forced us to face the emotions that have arisen from past failures, disappointments, and struggles?